Evaluasi Program Pendidikan di SMK: Systematic Literature Review Terhadap Logic Model dan Theory-Based Evaluation - Fadlul Amdhi Yul; Hadi Kurnia Saputra; Andre Yuberta; Arianto; Wakhinuddin Simatupang; Muhammad Anwar (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the application of the Logic Model and Theory-Based Evaluation in evaluating educational programs at Vocational High Schools (SMK), as well as to identify the advantages, limitations, and effectiveness of both approaches. The method used is a Systematic Literature Review (SLR) referring to PRISMA guidelines. Literature searches were conducted through scientific databases with a publication range from 2019 to 2026. From the selection process, 15 articles that met the inclusion criteria were obtained and analyzed qualitatively using a narrative synthesis. The research results indicate that the Logic Model approach is effective in mapping program structures systematically through the relationships between inputs, processes, outputs, and outcomes, making it easier to understand program flow and result achievements. Meanwhile, Theory-Based Evaluation is superior in explaining the mechanisms of change and the cause-and-effect relationships underlying program success. Nevertheless, this approach has a higher level of complexity and requires more in-depth data. The conclusion of this research shows that there is no single approach that is entirely superior, so the integration of Logic Model and Theory-Based Evaluation becomes the most effective strategy in producing a comprehensive, systematic, and evidence-based program evaluation. This integrative approach is recommended to improve the quality of educational program evaluations in vocational high schools (SMK).